RESEARCH OF VARIATIONS OF SEISMIC ACTIVITY IN CONNECTION WITH VARIATIONS OF STRUCTURE AND DYNAMICS OF THE EARTH'S RADIATION BELT - Sha. Zhantayev, Zhu.; Ya. Khachikyan, G.; Pulinets, S.A.; Zhumabayev, B.T.; Toyshiev, N.S. (Academic Scientific Journal of Computer Science, 2020)
For earthquakes with a magnitude of M≥4.5 that occurred on the planet in 1973-2017 (more than 220 thousand events in accordance with the NEIC USGS seismological catalog), the values of the McIlvine parameter (L) indicating the distance of geomagnetic lines to the center of the Earth at the equator, expressed in the radii of the earth are calculated, The histogram of the distribution of the number of earthquakes depending on the parameter L showed a decrease in their number with an increase in L, but two intervals stand out against the trend: 3.3≤ L ≥3.7 and 2.1≤ L ≥2.25, in which the number of earthquakes is statistically significantly decreased / increased relatively to the trend. Deviations are positively correlated with an decreased / increased population of these lines by high-energy particles in the radiation belt. After the magnetic storms devastate the external electron belt with the concomitant formation of rings of relativistic electrons in the inner magnetosphere around certain L, an increase in seismic activity occurs at the base of these lines on the earth's surface, but with a delay of ~ 2 months. So, after a magnetic storm on March 24, 1991, an additional radiation belt was formed around L = ~ 2.6, and on May 30, 1991, an M7.0 earthquake in Alaska occurred at the base of L = 2.69. After a magnetic storm on September 3, 2012, an additional belt formed around 3.0≤ L≤ 3.5, and on October 28, 2012, an M7.8 earthquake occurred off the coast of Canada at the base of L = 3.32. After a magnetic storm on June 23, 2015, a belt of relativistic electrons formed around L = 1.5-1.8, and in September 2015 seismic activity significantly increased at the base of these geomagnetic lines and it is interesting that at the same time on September 16, 2015, an M8.3 earthquake occurred in Chile, though at the base of the lower geomagnetic line L = 1.12.